Examining Adult Learning Through the Lens of Culture: A U.S. Perspective - Susan Yelich Biniecki; Haijun Kang (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2015)
This paper examines adult learning within United States based journals through the lens of culture. Four thematic areas from the literature are highlighted. These themes include: critically examining one's own and others' cultural stories; utilizing sociocultural approaches to facilitate or guide adult learning; developing and maintaining dialog; and incorporating strategies to improve people's cultural awareness and competency. Implications for practice are addressed throughout. A concluding discussion suggests areas for future research.